Pink Kakada (Jasminum multiflorum): A potential loose flower crop for winter production - Marappan, Kumaresan; Mariyappillai, Anbarasu (Indian Horticulture, 2025)
Jasminum multiflorum (Pink Kakada) is an excellent flower crop to grow in tropical, subtropical, and temperate regions. Pink Kakada has the characteristics of a year-round flowering habit, excellent keeping quality, colourful flower buds, and resistance to common pests and diseases, making it an economically significant crop for commercial cultivation. Pink Kakada produces the suckers and branches continuously and produces flowers in a terminal of every cyme. The peak season for flowering of pink Kakada is during the month of December. However, off-season flowering is a major constraint in commercially cultivated Jasminum species. The gap in the supply and demand for Jasmine flowers during the winter season highlights the need to find a solution, which may involve either forcing commercial species to flower during off-seasons or making use of underutilized Jasminum species that have year-round flowering habits. Pink Kakada is a potential crop grown instead of commercial jasmine species for the winter season. Commercialization of Pink Kakada reduces demand during the off-season, ensuring a steady supply of flowers for the market and increasing the economy of the growers.